'Transcorneal Electrical Stimulation Therapy May Have A Stabilization Effect on Multifocal Electroretinography for Patients with Retinitis Pigmentosa' - (:unkn) unknown (My University, 2021)
PURPOSE: To assess the effects of Transcorneal Electrical Stimulation (TES) on several measures of visual function in retinitis pigmentosa (RP). METHODS: This prospective, randomized, fellow-eye-controlled study includes 30 eyes of 15 RP patients. Each patient's eyes were randomly selected as treatment(TE) and control eye(CE), and 30 minutes/week TES applied for six months. Patient evaluations were done before and after TES including comprehensive ophthalmological examination, visual fields, full-field and multifocal (mf-) electroretinography (ERG), microperimetry, and optical coherence tomography. All parameters were compared before and after TES and between TE and CE. RESULTS: After TES, the mean signal amplitudes(MSA) in mf-ERG were stabilized in TE. MSA in CE decreased in every ring, reaching significance in fifth ring (847,15±393,94 and 678,77±282,66 nV, p=0.039, before and after TES, respectively). The changes in MSA of TE and CE were -0,38±295,53 and -185,15±332,62nV in second(p=0,046), 36,69±326,4 and -143,38±317,41nV in fourth(p=0,028), -17,46±333,07 and -168.38±297,14nV in fifth rings(p=0,046), respectively. The decrease in MSA between 2° to 20° midperipheral retina was significantly less in TE (-33,59±225,1nV) than CE (-205,56±345,1nV)(p=0,011). There were no siginificant changes in other parameters. CONCLUSIONS: The progression in mf-ERG might be stabilized with TES. Further studies with larger sample sizes and longer follow-up are needed to conclude that TES reduces RP progression.